Metabolomics, milk-oriented microbiota (MOM) and multipotent stem cells: the future of research on breast milk - Vassilios Fanos (Hygeia Press di Corridori Marinella, 2015)
The more we learn about human milk, the more we are forced to admit to our extraordinary ignorance about this liquid, considered miraculous from ancient times. This editorial deals with three themes of great importance today: metabolomics, milk-oriented microbiota (MOM) and multipotent stem cells. Metabolomics, also called the "new clinical biochemistry", is an approach based on the systematic study of the complete set of metabolites in a biological sample, in our case milk. Very few papers have been published on this topic. The human milk is anything but sterile! Today we know that it contains a quantity of bacteria (microbiota) of 50 genera and 200 species. The composition of human milk microbiota is highly individualized and unique for each mother and can have important effects on the colonization of the intestine and the short- and long-term health of the child. We speak of MOM. Finally, we also know that human milk contains stem cells whose function is not yet fully known. It appears that the stem cells of human milk pass through the intestinal barrier as well as that of the brain and migrate to settle in the brain and other organs and apparata, among which surely the thymus, pancreas and liver. Once they reach the neonatal tissue of destination, they appear to differentiate to assimilate and integrate in the tissue. For example, at the level of the brain stem cells from human milk may differentiate have become oligodendrocytes, astrocytes and neurons. Perhaps from the integration of knowledge in these three fields we could take further significant steps towards the understanding of the miracles of human milk.